Histological and ultrastructural evaluation of human decellularized matrix as a hernia repair device. (2nd January 2018) - Ghetti, Martina; Papa, Valentina; Deluca, Giovanni; Purpura, Valeria; Ruscelli, Paolo; Melandri, Davide; Capirossi, Daniela; Nigrisoli, Evandro; Minghetti, Paola; Bondioli, Elena; Cenacchi, Giovanna
ABSTRACT: Recently, interest has been increasing for human decellularized matrices, due to their ability to reduce numerous side effects related to hernia repair. To date, only animal studies investigated the biological interaction post-implant of human decellularized matrices for soft tissue repair. Therefore, the aim of this study was to evaluate the morphological response one year post implant of human decellularized matrix, through morphological analysis of human biopsies. The histological and ultrastructural results revealed a perfect cellular repopulation and neoangiogenesis, with minimal inflammatory response and a well-organized collagen matrix. The results have indicated that this scaffold can be an effective treatment for hernia.